The Nicene Line as Structural Principle for Christian Doctrine - Sanders, Fred (International journal of systematic theology, 2025)
Nicaea (both the 325 council and the creed that by 381 perfected its work) instantiates a structural principle for Christian doctrine, a principle called here the Nicene line. Its influence is evident in the main contours of doctrine, and it exerts continuing guidance for the teaching and research of individual theologians. The line that Nicaea draws is clearest in the second article of the Nicene Creed, which establishes the Son's particular filial identity with reference to his eternal relation to the Father before narrating his economic action of creation and of incarnation ‘for us and our salvation'. Construing the events of the New Testament as the disclosure of divine sonship, Nicaea thus draws a line between God and creation, locating the blessed Trinity above the line precisely in order to describe the divine work of transformatively blessing creatures below the line. This principle is classically elaborated in pro-Nicene theologies (illustrated here by Theodoret of Cyrrhus), and is already evident in Scripture (illustrated here by the argument of Ephesians).